Target-triggered, self-powered DNAzyme–MnO2 nanosystem: towards imaging microRNAs in living cells - Cui, Mei-Rong; Li, Xiang-Ling; Xu, Jing-Juan; Chen, Hong-Yuan (Chemical communications (Cambridge, England), 2019)
A target-triggered, self-powered strategy for in situ monitoring of intracellular microRNAs was fabricated via a versatile DNAzyme–MnO2 nanosystem, which integrates delivery, quenching, target recognition, self-supply of cofactors and signal amplification all in one.